True Blue - Baldacci, David (New York : Grand Central Pub., 2009)
Fresh out of prison, disgraced ex-cop Mason "Mace" Perry, along with the help of her police chief sister, aids Roy Kingman, a lawyer trying to track down the killer of one of his law partners, all while a U.S. attorney looks for any reason to put Mace back behind bars.
Keywords: Police -- Fiction; Revenge -- Fiction; Large print books; Washington (D.C.) -- Fiction